Vous êtes sur la page 1sur 6

Notes - TFM - ’1+1’ Universe

Samuel Barroso Bellido

1 Bogolubov Coefficients
In a two-dimensional Friedman-Lemaitre-Robertson-Walker (FLRB) Universe, we can define
the line element as:

ds2 = C (η ) dη 2 − dx2 ,

(1)
where η is the conformal time defined by adη = dt.
As an example, lets take:

C (η ) = A + B tanh(ρη ), A, B, ρ constants; (2)


and then, the scalar modes functions are:
1
uk (η, x ) = (2π )− 2 eikx χk (η ), (3)
where χk (η ) satisfy a Klein-Gordon equation kind:

d2
χk (η ) + k2 + C (η )m2 χk (η ) = 0.
 
2
(4)

Calculations
First, lets calculate the asymptotic behaviour at η → ±∞:
 2
 d χk (2η ) + ω 2 χk (η ) = 0, for η → −∞
dη in
2 , (5)
 d χk (2η ) + ω 2 χk (η ) = 0, for η → +∞
dη out

with:
( p
ωin = k2 + m2 ( A − B)
p . (6)
ωout = k2 + m2 ( A + B)
The solutions are well known as:
(
χk (η ) = N exp{−iωin η }, for η → −∞
, (7)
χk (η ) = N exp{−iωout η }, for η → +∞
with a normalization constant N.
To solve the general equation in terms of hypergeometric functions, lets take:

1
z= (1 + tanh(ρη )) , C (z) = A + B (2z − 1) , (8)
2

1
and knowing that:

d2 χk (η ) dz 2 d2 z dχk (η )
      
d dχk (η ) d dχk (η ) dz
= = + 2 , (9)
dη dη dη dz dη dz2 dη dη dz
we can rewrite (4) as:

d2 χ k ( z ) dχk (z) k2 + [ A + B(2z − 1)] m2


z (1 − z ) + ( 1 − 2z ) + χk (z) = 0. (10)
dz2 dz 4ρ2 z(1 − z)
Now, if we suppose χk (z) to be of the form:

χ k ( z ) = e f ( z ) y ( z ), (11)
where f (z) is an unknown function, we can rewrite it again as:

d2 y dy
 
d f (z)
z (1 − z ) 2 + 2z(1 − z) + (1 − 2z) +
dz dz dz
(  ! )
d2 f (z) d f (z) 2 d f (z) k2 + [ A + B(2z − 1)] m2

+ y z (1 − z ) + + (1 − 2z) + = 0. (12)
dz2 dz dz 4ρ2 z(1 − z)

Now, we can look for a function f (z) to obtain an hypergeometric differential equation:

d2 y dy
z (1 − z ) 2
+ [ c − ( a + b + 1) z ] − abz = 0. (13)
dz dz
That function clearly satisfy:

d f (z) α + βz
= , (14)
dz z (1 − z )
where α and β are constants to be calculated. Then:

d2 y dy
z (1 − z ) + [(2α + 1) + 2z( β − 1)] +
dz2 ( dz )
4ρ2 z2 ( β2 − β) + z 4ρ2 (2α + 1) β + 2Bm2 + 4ρ2 α2 + k2 + Am2 − Bm2
 
+y = 0. (15)
4ρ2 z(1 − z)

To do that, all into the curly brackets from (15) needs to be constant. With this function f (z),
we fulfil the condition if:

2 2 2
4ρ ( β − β) = −4ρ C

4ρ2 (2α + 1) β + 2Bm2 = 4ρ2 C . (16)

 2 2 2 2
4ρ α + k + Am − Bm = 0 2

The results are:



i
k2 + ( A − B)m2 = ± 2ρi ωin = sgn(α) 2ρi ωin
p


 α = ± 2ρ
β = 2ρi [−sgn(α)ωin ± ωout ] = 2ρi [−sgn(α)ωin + sgn( β)ωout ] . (17)

 C = β (1 − β )

2
Knowing f (z) we can built our hypergeometric equation:

d2 y dy
+z (1 − z )
[(2α + 1) + 2z( β − 1)] + yβ(1 − β) = 0, (18)
dz2 dz
and compared with (13), we have:
(
a = − β, b = (1 − β ), c = 2α + 1
, (19)
a = (1 − β ), b = − β, c = 2α + 1
showing the symmetry on a and b of the hypergeometric function.
Finally, we found the solution:

χk (z) = N 2 F1 ( a, b; c; z) exp{α ln(z) − (α + β) ln(1 − z)}, (20)


where N is the constant from the integration of f (z), and the hypergeometric function is defined
by:

( a)n (b)n zn
2 F1 ( a, b; c; z ) = ∑ (c)n n! , (21)
n =0

with (m)n the Pochhammer symbol:


(
1, n=0
(m)n = ; (22)
m(m + 1)(m + n − 1), n>0

and taking sgn(α) = +, sgn( β) = −, and defining ω± = 12 (ωout ± ωin ):



i
 a = 1 + ρ ω+
( 
α = 2ρi ωin

=⇒ b = ρi ω+ ; (23)
β = − ρi ω+ 
c = 1 + i ωin

ρ

and then the solution yields:

 
     
i i i
χk (z) = N 2 F1 1 + ω+ , ω+ ; 1 + ωin ; z ×
ρ ρ ρ
 
i i
× exp ωin ln(z) + ωout ln(1 − z) + K =
2ρ 2ρ
       
i
ωin i
ωout i i i
= Nz 2ρ (1 − z ) 2ρ
2 F1 1 + ω+ , ω+ ; 1 + ωin ; z =
ρ ρ ρ

 iωin
 
iωin iωout iωout
η − ln[2 cosh(ρη )] − − ln[2 cosh(ρη )]
=N e 2 e 2ρ e 2 η e × 2ρ

       
i i i 1
× 2 F1 1 + ω+ , ω+ ; 1 + ωin ; (1 + tanh(ρη )) =
ρ ρ ρ 2

3
 
ω+
= N exp −iω− η − i ln [2 cosh(ρη )] ×
ρ
       
i i i 1
× 2 F1 1 + ω+ , ω+ ; 1 + ωin ; (1 + tanh(ρη )) (24)
ρ ρ ρ 2
Using the following property of the hypergeometric function:

2 F1 [ a, b; c; z] = (1 − z)c−a−b 2 F1 [c − a, c − b; c; z] , (25)
we can write the normalized conjugate of the solution as:

 
∗ 1 iω−
χin
k (z) ≡ χk (z) = √ exp −iω+ η − ln [2 cosh(ρη )] ×
2ωin ρ
       
iω− iω− iωin 1
× 2 F1 1 + , ;1− ; (1 + tanh(ρη )) (26)
ρ ρ ρ 2
which we can proof that it is the in-solution since if η → −∞ the solution approaches the asymp-
totic solution N exp{−iωin η } found in (7).
This solution can be seen around the singular point z = 1 using another property of the hyper-
geometric function which states:

Γ(c)Γ(c − a − b)
2 F1 [ a, b; c; z] = 2 F1 [ a, b; a + b + 1 − c; 1 − z ] +
Γ(c − a)Γ(c − b)
Γ(c)Γ( a + b − c)
+ (1 − z ) c − a − b 2 F1 [ c − a, c − b; c − a − b + 1; 1 − z ] , if (|arg(1 − z )| < π ), (27)
Γ( a)Γ(b)
and then, the hypergeometric function in (26) yields:

       
iω− iω− iωin
2 F1 1+ , ;1− ;z =
ρ ρ ρ
   
Γ 1 − iωρin Γ − iωρout  
iω−
 
iω−
 
iωout
 
=     2 F1 1 + , ;1+ ;1− z +
Γ − iωρ+ Γ 1 − iωρ+ ρ ρ ρ
   
Γ 1 − iωρ - Γ iωρout 
iω+ iω+

iωout
 
+     2 F1 − ,1− ;1− ; 1 − z , (28)
Γ iωρ− Γ 1 + iωρ− ρ ρ ρ

and we obtain the way to expand the in-solution in terms of the out-solution:

out,∗
χin out
k (z) = αk χk (z) + β k χk ( z ), (29)
where the out-solution is:

 
1 iω−
χout
k (z) =√ exp −iω+ η − ln [2 cosh(ρη )] ×
2ωout ρ
       
iω− iω− iωout
× 2 F1 1 + , ;1+ ; 1 − z , (30)
ρ ρ ρ

4
and αk and β k are the Bogolubov coefficients:
       
iωin
r
ωout Γ 1 − ρ Γ − iωout
ρ
r
ωout Γ 1 − iω-
ρ Γ iωout
ρ
αk =    , βk =    . (31)

ωin Γ − + Γ 1 − + iω ωin Γ iω iω
ρ ρ ρ

Γ 1 + ρ

Now, using this properties of the gamma function:


π
Γ(1 + z) = zΓ(z), |Γ(ix )|2 = , (32)
x sinh (πx )
we can calculate their squared modulus as:
   
sinh2 πωρ + sinh2 πωρ −
|αk | =    , |βk | =    . (33)
sinh πωρ in sinh πωρout sinh πωρ in sinh πωρout

2 Stress-Energy Tensor
The general transformation of the renormalized stress-energy tensor and the Ricci scalar is
carried out by:

D E 1
D E 1 h ρν  −3 
Tµν [ ḡκλ ( x )] = ( g/ ḡ) 2 Tµν [ gκλ ( x )] + g Ω Ω;ρµ − 2Ω−4 Ω;ρ Ω;µ +
ren ren 12π  i
ν ρσ 3 −4 −3
+ δµ g Ω Ω;ρ Ω;σ − Ω Ω;ρσ , (34)
2

and
h i
R̄ = Ω−2 R + gµν 2(n − 1)Ω−3 Ω;µν + (n − 1)(n − 4)Ω−4 Ω;µ Ω;ν , (35)

for a n-dimensional spacetime; and then the stress-energy tensor for a conformally flat spacetime

gµν = C ( x )ηµν ≡ Ω2 ( x )ηµν , (36)


gives us:
D E 1
D E 1
Tµν [ gκλ ( x )] = (− g)− 2 Tµν [ηκλ ( x )] + θµν − Rδ ν , (37)
ren ren 48π µ
where
1
2 −1

θuu = −(1/12π )C 2 ∂u C 2

1 1
θvv = −(1/12π )C 2 ∂2v C − 2 , (38)

θuv = θvu = 0

given using the null coordinates:


(
u=η−x
, (39)
v=η+x
with line element:

5
ds2 = C (u, v)dudv, (40)
that gives the metric:
 
C 0 1
gµν = . (41)
2 1 0

Calculations
From the eq. (35) we can write the Ricci scalar as:
 
R = 2η µν Ω−3 Ω;µν − Ω−4 Ω;µ Ω;ν , (42)

so the calculations are limited to proof eq. (38). To do this, let compares eq. (34) and eq. (37):

  
1 1 
−3 −4

ν ρσ 3 −4 −3
θµν − ν
Rδ = η ρν
Ω Ω;ρµ − 2Ω Ω;ρ Ω;µ + δµ η Ω Ω;ρ Ω;σ − Ω Ω;ρσ ,
48π µ 12π 2
(43)
to obtain:
 i
1 h ρν  −3  1
θµν = η Ω Ω;ρµ − 2Ω−4 Ω;ρ Ω;µ + δµν η ρσ Ω−4 Ω;ρ Ω;σ − Ω−3 Ω;ρσ . (44)
12π 2
Lowering the index as θµγ = θµν gνγ = Ω2 θµν ηνγ we get:

Ω2 h
 i

−3 −4

−4 1 −3
θµγ = ηγν η ρν
Ω Ω;ρµ − 2Ω Ω;ρ Ω;µ + ηµγ η ρσ
Ω Ω;ρ Ω;σ − Ω Ω;ρσ . (45)
12π 2

and we can calculate the components, since Ω( x );t = 0:


 h i
Ω −3 ( Ω )2 = − Ω ∂2 Ω−1 = − 1 C 12 ∂2 C − 21

 θ
 xx = 12π 2 Ω
1 −2
Ω ;xx − Ω ;x 24π x 24π x
1 1
1 xx 2 −
θtt = 24π (ηtt η ) C 2 ∂ x C 2 . (46)


θ = θ = 0
xt tx

To perform the change of variable to null coordinates, one have to use the transformation
properties of the tensors:

∂yα ∂y β
θµν = θαβ , (47)
∂x µ ∂x ν
and finally:
1
2 −1

1
θuu = − 12π C 2 ∂u C 2

1 1
1
θvv = − 12π C 2 ∂2v C − 2 . (48)

θuv = θvu = 0